Legal Consistency of the Ta’zir Clause in the Financing of Musyarakah Mutanaqishah: An Empirical Study on Bank DKI Syariah - Amanda Chintya Dewi; Anggi Irawan; Rina Susanti Abidin Bahren; Rusdiana Priatna Wijaya (ASAS, 2026)
This study analyzes the legal consistency of the ta’zir clause in the financing of Musyarakah Mutanaqishah at Bank DKI Syariah through an empirical juridical study of the Financing Approval Letter and notarial deeds. The problem with the research lies in the difference in the formulation of the ta’zir clause in the two documents, which is 2.5% of the amount of arrears in the SPPP and 2.5% per day of the amount of arrears in the notarial deed. This study uses an empirical juridical method with a case study approach. The results of the study show that ta’zir is basically justified in sharia economic law as a sanction for customers who can afford but deliberately delay payment. However, the difference in clause formulation between SPPP and notarial deeds shows that there are inconsistencies that have the potential to weaken legal certainty, open up space for multiinterpretation, and disrupt sharia compliance if not immediately harmonized. Therefore, the harmonization of ta’zir clauses in all financing documents is needed as a preventive step so that the Musyarakah Mutanaqishah contract is structured clearly, proportionately, and provides balanced legal protection for banks and customers.